Digital Health Communication Between Healthcare Providers and Patients During COVID-19: A Narrative Review - Dela Riadi; Dewi Nirmala Sari (INJECT (Interdisciplinary Journal of Communication), 2026)
The COVID-19 pandemic accelerated the transformation of healthcare communication by shifting interactions between healthcare providers and patients from face-to-face encounters to digitally mediated communication. Digital communication platforms, including telemedicine, remote patient monitoring (RPM), virtual wards, mobile health applications, and messaging services, became essential channels for exchanging health information, monitoring patient conditions, providing consultation, and supporting continuity of care. This narrative review aimed to synthesize the existing evidence on digital health communication between healthcare providers and patients during COVID-19, with a particular focus on communication channels, information exchange, patient engagement, communication quality, and communication barriers. A purposive literature search was conducted using PubMed, Scopus, ScienceDirect, ProQuest, Embase, and other relevant sources. Twenty-six studies were included and analyzed using a narrative thematic approach. The findings indicate that digital health communication enhanced timely information exchange, facilitated continuous interaction between healthcare providers and patients, improved patient engagement in self-management, and strengthened communication throughout home-based care. The review also identified several communication challenges, including disparities in digital literacy, unequal access to communication technologies, privacy concerns, reduced interpersonal interaction, and variations in communication practices across healthcare settings. Overall, digital health communication has become a fundamental component of interdisciplinary healthcare communication by supporting accessible, patient-centered, and continuous communication during public health emergencies. Future implementation should strengthen communication quality, promote digital inclusion, and develop communication strategies that foster effective patient–provider interaction beyond the COVID-19 pandemic.